STUDY ON THE MASS BREEDING OF Euplectrus n. sp. close up comstockii PARASITE OF Anticarsia gemmatalis - PULIDO-FONSECA, JAIME (Revista Colombiana de Entomología, 1978)
Euplectrus n. sp. cerca comstockii Howard is an important larval parasite of the velvet bean caterpillar of soybean Anticarsia gemmatalis Hübner, a main insect pest of soybean in the Cauca Valley (Colombia). This investigation was conducted at the experimental station of the "Instituto Colombiano Agropecuario (ICA)" in Palmira, had as main objectives the study of its biology, behavior in relation to other possible hosts, and the necessary factors for its mass rearing. It was found that at 240C and 72,8% R.H., the mean duration of the different developmental stages in days was egg: 1,75; larva: 5,0; prepupa: 0,95 and pupa 5,50. The longevity of the adult females was found to be 10 - 32 days and of the males 7 - 14 days, both fed with a sugar solution. The sex ratio between females and males was 4:1. The highest number of eggs laid for 20 days was 75. Fourth instar larvae of A. gemmatalis were preferred by the parasite for laying their eggs; these larvae stopped feeding 4 to 5 days after parasitation. Larvae of Diatraea sacharalis F. were no parasitized by E. n. sp. The storage of mature parasite pupae for more than one week at 5-6°C and 750/o R.H. was unfavorable for the emergence, mating, longevity, and vigor of the adults.